2010
DOI: 10.5012/bkcs.2010.31.02.344
|View full text |Cite
|
Sign up to set email alerts
|

TiO2/Carbon Composites Prepared from Rice Husk and the Removal of Bisphenol A in Photocatalytic Liquid System

Abstract: The improved photocatalytic performance of a carbon/TiO2 composite was studied for the Bisphenol A (BPA) decomposition. Titanium tetraisopropoxide (TTIP) and a rice husk from Korea were heterogeneously mixed as the titanium and carbon sources, respectively, for 3 h at room temperature, and then thermally treated at 600 o C for 1 h in H2 gas. The transmission electron microscopy (TEM) images revealed that the bulk carbon partially covered the TiO2 particles, and the amount that was covered increased with the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The overall achieved photodegradation percentages of BPA in the framework of this work are comparable to those reported in the literature under similar reaction conditions using composites. For instance, 80% of degradation of BPA (11.4 ppm) in 24 h using TiO 2 /zeolite, and 75% of degradation of BPA (15 ppm) using TiO 2 /carbon in 5 h . In the present study, 47% of BPA (10 ppm) was decomposed in 8 h using the 8% Ag/ZnO‐PAA composite.…”
Section: Resultssupporting
confidence: 47%
“…The overall achieved photodegradation percentages of BPA in the framework of this work are comparable to those reported in the literature under similar reaction conditions using composites. For instance, 80% of degradation of BPA (11.4 ppm) in 24 h using TiO 2 /zeolite, and 75% of degradation of BPA (15 ppm) using TiO 2 /carbon in 5 h . In the present study, 47% of BPA (10 ppm) was decomposed in 8 h using the 8% Ag/ZnO‐PAA composite.…”
Section: Resultssupporting
confidence: 47%
“…This is an evidence for strong surface attachment and interactions between TiO 2 and lignin, which is desired. Kim et al 36 also observed a similar peak in the XRD of TiO 2 -carbon composites using rice husk as the carbon precursor at high loading. The crystallite sizes of Aeroxide® TiO 2 , and TiO 2 in DM, WMH, WMA and WMW mixtures were similar, i.e.…”
Section: Effect Of Ball Milling On Lignin-tio 2 Mixturementioning
confidence: 60%
“…[11][12][13][14][15][16] Recently phenols have also been removed with new adsorbents and/or reactions. [17][18][19] Mesoporous carbon, CMK-3 is a fascinating material and exhibits a high surface area, a large pore volume, narrow pore size distribution, and well-ordered mesoporous structure. 20,21 CMK-3 has been widely used as adsorbents for several chemicals including biomaterials such as L-histidine and vitamine E. [22][23][24][25][26][27][28] CMK-3, with or without modification, has also been used in the removal of phenol.…”
Section: 2mentioning
confidence: 99%